Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1128/aem.71.12.8587-8596.2005
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Expression of Fructose 1,6-Bisphosphatase in Corynebacterium glutamicum Increases In Vivo Flux through the Pentose Phosphate Pathway and Lysine Production on Different Carbon Sources

Abstract: The overexpression of fructose 1,6-bisphosphatase (FBPase) in Corynebacterium glutamicum leads to significant improvement of lysine production on different sugars. Amplified expression of FBPase via the promoter of the gene encoding elongation factor TU (EFTU) increased the lysine yield in the feedback-deregulated lysine-producing strain C. glutamicum lysC fbr by 40% on glucose and 30% on fructose or sucrose. Additionally formation of the by-products glycerol and dihydroxyacetone was significantly reduced in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
153
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(158 citation statements)
references
References 37 publications
3
153
0
Order By: Relevance
“…Li ϩ -sensitive phosphatases are putative targets for lithium therapy in the treatment of manic depressive patients (4), whereas FBPases are targets for the development of drugs for the treatment of noninsulindependent diabetes (5,6). In addition, FBPase is required for virulence in Mycobacterium tuberculosis and Leishmania major and plays an important role in the production of lysine and glutamate by Corynebacterium glutamicum (7,8).…”
mentioning
confidence: 99%
“…Li ϩ -sensitive phosphatases are putative targets for lithium therapy in the treatment of manic depressive patients (4), whereas FBPases are targets for the development of drugs for the treatment of noninsulindependent diabetes (5,6). In addition, FBPase is required for virulence in Mycobacterium tuberculosis and Leishmania major and plays an important role in the production of lysine and glutamate by Corynebacterium glutamicum (7,8).…”
mentioning
confidence: 99%
“…Metabolic flux studies on glucose, fructose, and sucrose identified fructose 1,6-bisphosphatase as a non-obvious target [110,111]. Subsequent amplified expression of the fbp gene indeed increased lysine yield on glucose, fructose, and sucrose up to about 40% [128]. Hereby, the mutant with overexpression of fructose 1,6-bisphosphatase exhibited 10% enhanced PPP flux.…”
Section: Metabolic Engineering Of Nadph Supplymentioning
confidence: 90%
“…In C. glutamicum, glucose 6-phosphate dehydrogenase, 6-phosphogluconate dehydrogenase, isocitrate 13 C flux analysis: [112] (white circles), [125] (gray circles), [126] (black circles), [127] (white squares), [111] (gray squares), [111] (black squares), [128] (white triangles), [116] (gray triangles), [26] (black triangles), [129] (white diamonds), [115] (gray diamonds), [120] (black diamonds), [76] (white hexagons), and [118] (gray hexagons). The flux reversibility at the pyruvate node is defined as the ratio of the back flux to the anaplerotic net flux [130] 36 C. Wittmann dehydrogenase, and malic enzyme catalyze NADPH generating reactions, whereas NADPH consuming reactions comprise growth with a stoichiometric demand of 16.4 mmol NADPH (g biomass) À1 [34] and overproduction.…”
Section: Metabolic Fluxes Of Nadph Metabolismmentioning
confidence: 99%
See 2 more Smart Citations